How thyroid hormone disorder affect the expression of genes related to neurodegeneration in the hippocampus tissue of rats: An experimental study - Melek Altunkaya; Ercan Babur; Esra Tufan; Cem Süer; Nurcan Dursun (Journal of Clinical Sciences, 2024)
Background Thyroid hormones (THs) have important effects on many organ systems, including the hippocampus, by modulating gene transcription. Therefore, deviations from the normal reference range of this hormone cause vital changes. However, it is not well understood how these hormones affect the expression of genes involved in the Akt1/Gsk3ß signaling pathway in hippocampus tissue. The study investigated the changes in gene expression in eight genes related to neurodegeneration in the hippocampus tissue of rats with TH disorder (Gsk3ß-mRNA, Cdk5-mRNA, Akt1-mRNA, Mapt-mRNA P35 [Anxa]-mRNA, Capn1-mRNA, Bace1-mRNA, and Psen2-mRNA). Methods Twenty-two male rats were split into three groups as control, hypothyroidism, and hyperthyroidism. Propylthiouracil was given in drinking water for 21 days to induce hypothyroidism. L-thyroxine was administered for 21 days to induce hyperthyroidism. The levels of genes in the hippocampus were measured with the reverse transcription-polymerase chain reaction method. Results While free thyroxine (fT4) levels in blood plasma were found to be lower in the hypothyroidism group than in the control group, fT4 levels in blood plasma were found to be higher in the hyperthyroidism group. The mRNA expression levels of Cdk5, Mapt, P35, Akt1, Psen2, and Bace1 genes evaluated in hippocampus tissue showed significant differences between the groups. Conclusion THs are essential for the expression of certain genes, and these genes need to be expressed within a certain range for the body to function properly. Changes in hormone levels can partially change the expression of Akt1/Gsk3ß-mRNA, which is also associated with learning and memory.